Menelaah Sejarah Peradaban Islam dengan Metode Kajian Sejarah - Angkat, Maimanah (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2024)
The aim of this research is to clarify the history of Islamic civilization and historical research methods. In studying the history of Islamic civilization and historical research methods, this method (library research) is used by studying a large number of books, periodicals, periodicals and life stories related to the problems and objectives of Masu's research. Data collection with the results of previous research, data supporting research themes and historical research methods in the history of Islamic civilization. The research process begins with certain stages: the search for relevant information, analysis and subsequent development of the results, as well as the presentation of new insights into the history of Islamic civilization and historical research methods. Civilization is evidence of cultural progress and development from time to time. On the other hand, Islam is a holy religion and Allah SWT has revealed it to all mankind through His Messenger, Prophet Muhammad SAW, through His guidelines, namely the Al-Quran and Hadith. There are two methods used to describe the history of Islamic civilization: the historical excavation method (historiography) and the historical method. General methods in extracting history (writing history) include accurate verbal and oral methods, observation methods which involve direct observation, and recording methods which involve careful and thorough study of all existing documents. Meanwhile, the historical method is a method that is applied after carrying out historical excavation methods. The methods used include descriptive methods (description), comparative methods (comparison), and comprehensive analysis methods (critical analysis and drawing conclusions).